Utilising Generative AI in the Classics classroom - David Peddar (The Journal of Classics Teaching)
The place Generative AI (Gen AI) has within education and schooling has been subject to much scrutiny. Its ever-evolving and growing nature has left many educators and other stakeholders scrambling with questions about how to adapt its approach, methodology and place within the classroom. Gen AI has also been shown to have particularly efficacy in the area of Classical languages teaching. It also has challenges (Ross, 2023). The following paper explores a proactive approach to utilising Gen AI technology and programs within a Latin classroom NESA Stage 4-5/ MYP Years 1-3 in Australia (ages 11-16) (NESA: New South Wales Education Standards Authority. MYP: Middle Years Programme). It also develops some approaches to facilitate students’ reflection so as to improve their understanding of the uses and abuses of Gen AI platforms in their own learning.